2009
DOI: 10.1007/s00253-009-1951-6
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of microbiological sulfide oxidation by methanethiol and dimethyl polysulfides at natron-alkaline conditions

Abstract: To avoid problems related to the discharge of sulfidic spent caustics, a biotechnological process is developed for the treatment of gases containing both hydrogen sulfide and methanethiol. The process operates at natron-alkaline conditions (>1 mol L −1 of sodium-and potassium carbonates and a pH of 8.5-10) to enable the treatment of gases with a high partial CO 2 pressure. In the process, methanethiol reacts with biologically produced sulfur particles to form a complex mixture predominantly consisting of inorg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 36 publications
2
19
1
Order By: Relevance
“…All experiments were performed at 35 ˚C (DC10, Thermo Haake, Germany) which is in agreement with the conditions in the lab-scale fed-batch setup. As temperature and medium composition were similar to previous studies, a proper comparison of our results can be performed (De Graaff et al., 2012; Klok et al., 2013; Roman et al., 2015; Van Den Bosch et al., 2009).
Fig.
…”
Section: Methodssupporting
confidence: 74%
“…All experiments were performed at 35 ˚C (DC10, Thermo Haake, Germany) which is in agreement with the conditions in the lab-scale fed-batch setup. As temperature and medium composition were similar to previous studies, a proper comparison of our results can be performed (De Graaff et al., 2012; Klok et al., 2013; Roman et al., 2015; Van Den Bosch et al., 2009).
Fig.
…”
Section: Methodssupporting
confidence: 74%
“…Otherwise, in route II, dimethyl trisulfide was detected, which might be derived from intermolecular interaction of DMDS. Similar route could also be found in some previous studies (Chin and Lindsay, 1994;van den Bosch et al, 2009). Meanwhile, according to the kinetics results, both routes can lead to the mineralization of DMDS into CO 2 , H 2 O and sulfate after a series of degradation steps (Wei et al, 2013).…”
Section: Identification Of the Biodegradation Intermediatessupporting
confidence: 68%
“…Instead, we detected accumulation in the bioreactor suspension up to a total concentration of ∼16 µM S at −450 mV (Figure 3(a)). Van den Bosch et al [27] studied the inhibitory effect of DMDS and DMTS on the bacterial oxidation of sulphide and found that DMTS is more toxic to SOB than DMDS. Besides dimethyl polysulphanes, also inorganic polysulphide anions were produced from the reaction between methanethiol and elemental sulphur (Equation (6)), as reflected by the somewhat higher S 2−…”
Section: Methanethiol Removal From Sour Gasmentioning
confidence: 99%